PENGARUH PERTUMBUHAN EKONOMI, TINGKAT PENDIDIKAN DAN PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI SUMATERA SELATAN DALAM PERSPEKTIF EKONOMI ISLAM TAHUN 2017-2020 - Laura Nindya Asmananta; Emi Yulia Siska; Abdullah Sahroni (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to determine the relationship between economic growth, education level, and unemployment on poverty levels in the province of South Sumatra in 2017 – 2020. The method in this study is quantitative with secondary data obtained from the Central Statistics Agency of South Sumatra and a sample of 17 districts and cities. The data analysis technique used is the panel data regression method with E-Views 10. The results of this study indicate that economic growth, education level, and unemployment have a significant effect on the poverty level simultaneously, while partially the level of education and unemployment influence the poverty level and the opposite of economic growth has no impact on the level of poverty.